Modern Theological Debates of Hell in the USA - Sydney Sadowski (Polonia Sacra)
Among the differing Christian denominations there are various viewpoints regarding hell. This article presents differing viewpoints of the theological questions concerning hell that have been debated over the last ten years (2010–2020) in the United States in the theological arena as well as the popular press. The positions of annihilationism, universalism, and the traditional viewpoint are be surveyed. The differing philosophical, theological and biblical are presented for each general category. The article strives to give a general overview of the various theologies and to show that such theological investigation is of urgent importance for Christians today.